2019
DOI: 10.1136/bjophthalmol-2018-313364
|View full text |Cite
|
Sign up to set email alerts
|

Right-angled vessels in macular telangiectasia type 2

Abstract: PurposeTo evaluate the role of right-angled vessels (RAVs) during disease progression in macular telangiectasia type 2 (MacTel).MethodsIn this study, 100 eyes of 52 patients and 52 eyes of 26 age-related controls were examined using fundus photography, spectral-domain optical coherence tomography (SD-OCT), OCT angiography (OCT-A) and fundus fluorescein angiography (FFA). Two masked readers graded fundus photographs of patients’ eyes into five disease stages according to Gass and Blodi, and evaluated all eyes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…The latter include pigmentary changes, possibly deriving from migrating RPEcells, neurodegenerative processes, cellular debris, and vascular alterations. [21][22][23] Although a correlation of hyperreflectivity with disease progression has been proposed, its functional relevance has yet not been evaluated. In this study, we used an approach that quantified hyperreflective changes in MacTel.…”
Section: Discussionmentioning
confidence: 99%
“…The latter include pigmentary changes, possibly deriving from migrating RPEcells, neurodegenerative processes, cellular debris, and vascular alterations. [21][22][23] Although a correlation of hyperreflectivity with disease progression has been proposed, its functional relevance has yet not been evaluated. In this study, we used an approach that quantified hyperreflective changes in MacTel.…”
Section: Discussionmentioning
confidence: 99%
“…We could commonly find clustered HF at the foveola in eyes with only an inner retinal hyporeflective cavity. HF could be related to various causes or signs in MacTel type 2 2 , 12 15 . Baumüller et al 12 suggested that HF might represent an early sign of a neurodegenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] In a recent qualitative analysis, we showed an increase of flow voids and irregular appearance of the choriocapillaris in eyes with advanced (but non-proliferative) disease stages. 36 In this study, we quantified these changes and found an overall reduced and more irregular perfusion of the choriocapillaris indicated by a significant increase of flow voids and reduced kurtosis of signal intensity distribution. Notably, these findings were already observed in early disease stages, indicating an earlier affection of the choroid than previously expected.…”
Section: Discussionmentioning
confidence: 80%
“…In line with recent findings, 12,35 we observed the presence of pathologic vascular structures in the avascular layer of eyes with advanced and neovascular disease stages, but not in early stages. Though different studies proposed a descent of vascular changes to the outer retina, 12,35,36 segmentation of retinal layers in eyes with advanced disease stages may be challenging, and a collapse of retinal layers due to increasing atrophy may at least in part be responsible for the observed phenomenon.…”
Section: Discussionmentioning
confidence: 99%